2017
DOI: 10.18203/2349-3291.ijcp20170723
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of acute kidney injury in neonatal sepsis in a tertiary care centre

Abstract: Original Research ArticleClinical profile and outcome of acute kidney injury in neonatal sepsis in a tertiary care centre Divya Durga*, Sudha Rudrappa INTRODUCTIONNeonatal sepsis is one of the major global health problems. Thirty eight percent of all childhood deaths occur in neonates 1 . Ninety nine percent of these neonatal deaths occur in low-income and middle-income countries.1 In developing countries like India, sepsis contributes to 37% of all neonatal deaths.2 As per the National Neonatal Perinatal Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Total number of septic neonates enrolled were less (only 50) as compared to our study. 21 Gaurav et al in their study in India showed 21.49% (34 out of 107) septic neonates developed acute renal failure. This is slightly lower percentage than our value as number of patients in their study was less as compared to our study.…”
Section: Resultsmentioning
confidence: 94%
“…Total number of septic neonates enrolled were less (only 50) as compared to our study. 21 Gaurav et al in their study in India showed 21.49% (34 out of 107) septic neonates developed acute renal failure. This is slightly lower percentage than our value as number of patients in their study was less as compared to our study.…”
Section: Resultsmentioning
confidence: 94%
“…Sepsis has been consistently associated as a risk factor for development of AKI in various studies conducted around the world contributing to as high as 78% cases in some neonatal studies. 28 Another study from India by Mathur NB et al, shows that out of 200 newborns with sepsis, 26% developed AKI. 29 The newborns with sepsis are thought to be predisposed for AKI as a result of hypotension secondary to sepsis and a direct damaging effect on renal microvasculature.…”
Section: Discussionmentioning
confidence: 99%